Cognitive Stimulation (An Approach to Cognitive Impairment) Time for Action Now! - Sonia Singh; Achla Dagdu Gaikwad (Indian Journal of Psychiatric Nursing)
"Gold agers are our worthy blessing, value, and assist them to live with dignity" Aging is a natural unrestrictive and irreversible process and an age of change in all dimensions including physical, psychological, social, and environmental. Cognition simply means to the psychological processes and activities related to understanding things, making judgments, memory, and reasoning in comparison to emotional and volitional process. The decrement of this cognitive function is known as cognitive impairment. Old age is the age of cognitive impairment the time for action is now! As increasing age is the greatest risk factor for cognitive impairment as its prevalence rate is found high worldwide, and as the baby boomer generation passes age 65, the number of people living with cognitive impairment is expected to jump dramatically. The prevention and treatment of cognitive impairment have been an important need and responsibility of the health sector area. Apart from the pharmacotherapy, there are other approaches and programs such as occupational therapy, environmental approach, brain training, dietary plan, executive cognitive structuring program, and cognitive stimulation therapy (CST) found effective in improving cognitive functions. CST has been popular, cost-effective, and successful for improving cognitive function and it is theme-based multicomponent therapy which focuses on cognitive abilities and can be given by the professional nurses, an occupational therapist, or a caregiver. The current concept article throws a flashlight on CST as a therapeutic approach to stimulate cognitive functions in geriatrics.